2020
DOI: 10.3390/pathogens9020107
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Strongyloidiasis in Spain: A Hospital-Based Study

Abstract: Introduction: Strongyloidiasis is a prevailing helminth infection ubiquitous in tropical and subtropical areas, however, seroprevalence data are scarce in migrant populations, particularly for those coming for Asia. Methods: This study aims at evaluating the prevalence of S. stercoralis at the hospital level in migrant populations or long term travellers being attended in out-patient and in-patient units as part of a systematic screening implemented in six Spanish hospitals. A cross-sectional study was conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
0
1
Order By: Relevance
“…In a recent meta-analysis of the prevalence of strongyloidiasis in migrants from endemic areas who reside in Spain, the authors found an overall prevalence of 14% in Latin Americans [ 30 ]. Our study showed a lower prevalence than that (6% in children and adolescents and 12% in adults; 11% overall), but a similar proportion as another study performed in Spain, where the prevalence was 10.9% in patients from South America [ 3 ].…”
Section: Discussionsupporting
confidence: 81%
“…In a recent meta-analysis of the prevalence of strongyloidiasis in migrants from endemic areas who reside in Spain, the authors found an overall prevalence of 14% in Latin Americans [ 30 ]. Our study showed a lower prevalence than that (6% in children and adolescents and 12% in adults; 11% overall), but a similar proportion as another study performed in Spain, where the prevalence was 10.9% in patients from South America [ 3 ].…”
Section: Discussionsupporting
confidence: 81%
“…During the study period, 2024 individuals attending six hospitals were screened for strongyloidiasis. Results of the seroprevalence data published elsewhere [ 9 ] showed an overall seroprevalence of S. stercoralis of 9.04% (95%CI 7.76–10.31).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals at risk of being infected with S. stercoralis were identified (namely those having resided in an endemic country for more than one year, and having attended the hospital for any reason) and a systematic screening for S. stercoralis was offered to patients attending any of the six participating hospitals. This screening was performed in the tropical medicine and international health, transplant, haematology and oncology, pneumology, infectious diseases (including HIV) and systemic diseases departments (including rheumatology and dermatology) of each hospital [ 9 ]. However, it should be added that although not all patients were immunosuppressed, the reasons for hospitalization in those units were always conditions related to such units.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations